Mainamati--Lalmai - Hossain, M. Mosharraf, 1950-; Deoẏāna, Tophāẏela Āhameda; Bangladesh. Pratnatattva Adhidaptara (Dhaka : Dibyaprakash, 2004)
Articles on antiquities and archaeological excavations in Mainamati and Lālmai Hills regions in Bangladesh.
Includes bibliographical references (p. 6).
Keywords: Excavations (Archaeology) -- Bangladesh -- Mainamati Region; Excavations (Archaeology) -- Bangladesh -- Lālmai Hills Region (Bangladesh); Mainamati Region (Bangladesh) -- Antiquities; Lālmai Hills Region (Bangladesh) -- Antiquities